El Derecho del Trabajo en el Perú y su proceso de constitucionalización: Análisis especial del caso de la mujer y la madre trabajadora - Landa Arroyo, César (2014)
In order for labor rights to be recognized as fundamental in the Social and Democratic State of Law, Labor Law had to go through a process of constitutionalization, providing protection to all workers. However, for reasons of historical discrimination, a group of peopleis subject to “special protection” in the contextof labor relations: Working mothers.In this paper, the author presents a complete analysis of the fundamental rights of women in labor relations, stating the reasons for which corresponds to provide “special protection” to women in general, but in particular to working mothers.